Construction and application of a refined index for measuring the regional matching characteristics between water and land resources. (August 2018) - Liu, Dong; Liu, Chunlei; Fu, Qiang; Li, Mo; Faiz, Muhammad Abrar; Khan, Muhammad Imran; Li, Tianxiao; Cui, Song
Highlights: BAWR is introduced as the water resource quantity parameter. The Gini coefficient model is proposed based on the BAWR. A refined index for measuring matching characteristics based on BAWR is constructed. The rationality of the Gini coefficient model and refined index are analyzed. Abstract: In accordance with national policies, the Jiansanjiang Administration of Heilongjiang Province in China has assumed a heavy task of grain production in recent years. The spatial matching status of water and land resources is a prerequisite for grain production. To analyze the potential for grain production objectively, the matching characteristics of agricultural water resources and land resources in Jiansanjiang Administration were analyzed for this paper. The spatial distribution pattern of the water and land resources was analyzed, and the amount of broadly-defined agricultural water resources (BAWR) and cultivated area were introduced as the water resource and land resource quantity parameters, respectively. The Gini coefficient model for agricultural water and land resource matching and the model for measuring the matching index between the BAWR and land resources (MIBAWRLR) were then constructed to evaluate the degree of matching between agricultural water and land resources in Jiansanjiang Administration and 15 farms in the region. Based on the Cobb-Douglas all-factor production function, the input–output model of agricultural production was built, with the grain yield per hectare used as the explained variable and basic, technological, and natural factors as the explaining variables. The results are as follows: ① The results of the MIBAWRLR indicate that the matching situation between agricultural water resources and land resources in Jiansanjiang Administration has improved, which was consistent with the results of the Gini coefficient model. The matching situation on the farms of Jiansanjiang Administration worsened from south to north, and the spatial matching pattern was consistent with the spatial distribution of the proportion between blue water and green water at each farm, i.e., the matching situation on a farm with a high proportion of blue water was satisfactory. ② According to the input–output model of agricultural production, introducing the BAWR into the established models as the characteristic parameter of water resource quantity is scientific and reasonable.